Impact of Falls and Sleep Quality on Quality of Life among Older Men with Lower Urinary Tract Symptoms due to Benign Prostatic Hyperplasia - Kaosaiyanant, Pitchaya; Roopsawang, Inthira; Aree-Ue, Suparb (Pacific Rim International Journal of Nursing Research, 2023)
Suffering from lower urinary tract symptoms in male older adults with benign prostatic hyperplasia affects quality of life profoundly. Lower urinary tract symptoms may precipitate to fall and poor quality of sleep. Less is known of the impact of falls and sleep quality on quality of life. This cross-sectional study aimed to determine the impact of falls and sleep quality on quality of life in this population. The participant was 140 older males, diagnosed with benign prostatic hyperplasia, presented with lower urinary tract symptoms, and no history of prostatic surgery. Structured interview with questionnaires—Demographic and Health Record Form, International Prostate Symptom Score, Pittsburgh Sleep Quality Index, and European Quality of Life—Five Dimension—was conducted at outpatient urological surgery unit at a tertiary care hospital in Bangkok, Thailand. Descriptive statistics and multiple-logistic regression with bootstrapping analysis were used for data analysis. Results revealed that majority of the participants reported falls and poor sleep quality, while nearly half had poor quality of life. Moderate lower urinary tract symptoms severity including nocturia, frequency, and urgency were predominantly identified. The predictive model explained 36.7% and correctly classified 74.3% of the cases. Significantly, those who experienced falls last year, and poor sleep quality increased the risk of developing the poor quality of life by 2.43 to 20.68-fold and 4.90-fold, respectively. Findings suggest that nurses should focus on preventing falls and poor sleep quality to improve quality of life. Proactive identification or specific symptom assessment, particularly falls history, sleep quality, and urinary symptoms severity during the treatment, is of concern in older men with lower urinary tract symptoms.